On certain subclass of p-valent functions with positive coefficients - Anas Aljarah,; Maslina Darus, (Penerbit Universiti Kebangsaan Malaysia, 2014)
In this article, a certain differential operator , k ( ) p S f z α,β,λ,δ and a subclass S n,p(α,β,δ,λ, p) for analytic functions with positive coefficients of the form Σ∞ = + = + 1 ( ) n p n n f z z p a z are introduced. Some properties such as the coefficients inequalities, distortion theorem, radii of starlikeness and convexity, closure theorems and extreme points are given. A class preserving an integral operator is also stated.